Measuring the Impacts of Community-based Grasslands Management in Mongolia's Gobi - Leisher, Craig; Hess, Sebastiaan; Boucher, Timothy M.; van Beukering, Pieter; Sanjayan, M. (PLOS ONE, 2012)
We assessed a donor-funded grassland management project designed to create both conservation and livelihood benefits in the rangelands of Mongolia's Gobi desert. The project ran from 1995 to 2006, and we used remote sensing Normalized Differential Vegetation Index data from 1982 to 2009 to compare project grazing sites to matched control sites before and after the project's implementation. We found that the productivity of project grazing sites was on average within 1% of control sites for the 20 years before the project but generated 11% more biomass on average than the control areas from 2000 to 2009. To better understand the benefits of the improved grasslands to local people, we conducted 280 household interviews, 8 focus group discussions, and 31 key informant interviews across 6 districts. We found a 12% greater median annual income as well as a range of other socioeconomic benefits for project households compared to control households in the same areas. Overall, the project generated measurable benefits to both nature and people. The key factors underlying project achievements that may be replicable by other conservation projects include the community-driven approach of the project, knowledge exchanges within and between communities inside and outside the country, a project-supported local community organizer in each district, and strong community leadership.